CONSTRUCTIVIST GROUNDED THEORY IN QUALITATIVE RESEARCH FOR SOCIAL JUSTICE: PURPOSE, PROCESS, PROMISE - Keane, Elaine (2025)
Grounded theory is the most cited qualitative methodology, and its popularity is continually increasing through researchers’ engagement with its constructivist school. In this short paper, I explore its core purpose, history, and development over time, including its ‘contested’ nature, and the constructivist school’s increasing emphasis on social justice-oriented research through its pragmatist roots. Next, I examine constructivist grounded theory’s process, examining its core features and how these translate into specific strategies, as well as constructivist ‘adaptations’. Here, I also consider examples from education and nursing social justice-oriented research that have employed constructivist grounded theory. Finally, I end by considering the promise of the methodology, first by outlining some key challenges in its use, and finally by emphasising the significant potential of the methodology for social justice research into the future.